Education Character in the Era of Globalization: Facing the Challenges of the Modern World - Herlina, Herlina; Arismunandar, Arismunandar; Tolla, Ismail (International Journal of Engineering, Science and Information Technology, 2024)
Character education is a fundamental element in the education system, especially in the era of globalization, which brings cultural, social, and technological challenges. In Indonesia, character education faces various challenges, such as the influence of foreign cultures, individualism, and inequality in access to education. A values-based approach that centers on local culture is highly relevant to address these challenges. This strategy involves reinforcing traditional values through multicultural education and internalizing local cultural values at various societal levels, including families, schools, and communities. Studies have shown that integrating local values, such as tolerance, cooperation, and religiosity, can strengthen character education, making it more relevant to modern needs. Helius Sjamsuddin emphasized the importance of educational history as a foundation for building sustainable character education based on national culture. This study employs a literature review methodology as a scientific approach to collect, analyze, and synthesize information from various written sources. This study applied a descriptive approach. We collected data from multiple sources such as books, scientific journals, policy documents, articles, and research reports. The results of the analysis indicate that character education in Indonesia faces complex challenges due to globalization. These challenges impact both individuals and the education system, including the influence of foreign cultures, technology, and changes in students' mindsets. The proposed strategies include implementing local values, the positive utilization of technology, and the involvement of societal elements in the education process. Holistic-based character education can help the younger generation face global dynamics without losing their cultural and moral identity.